Lipase catalysed esterification of methyl glucopyranoside with selected aliphatic carboxylic acids : investigation on reaction parameters and surfactant properties / Maryam Farhana binti Kamel Ariffin - Kamel Ariffin, Maryam Farhana (2013)
Carbohydrate esters are non-ionic biodegradable surfactant that possessed wide range of hydrophilic-lipophilic balance (HLB) value. It has been extensively produced via conventional chemical esterification route. This resulted in a number of disadvantages e.g. environmental pollution and personnel safety. Enzyme catalyzed production of carbohydrate esters is viewed as an alternative route to chemical synthesis. Lipase belongs to hydrolase, a green and safer family that has been widely utilized in synthetic steps. Conventionally, lipase is known for its capability to hydrolyze triacylglyceride in an aqueous system. On the contrary, lipase exhibits esterase activities in the microaqueous system.In this study, lipase-catalyzed esterification reaction and properties of synthesized carbohydrate esters were investigated. Methyl α-D-glucopyranoside as acyl group acceptor and different carbon atom chain length of carboxylic acids as the acyl group donor (hexadecanoic acid, tetradecanoic acid and dodecanoic acid) were applied in the esterification. Full factorial experimental design was used to study the effects of different process parameters toward lipase-catalyzed esterification. Methyl 6-Ohexadecanoyl- α-D-glucopyranoside was used as the model carbohydrate ester in the study. It was found via statistical analysis (α = 0.05) that process parameters viz.substrates mol ratio (acyl acceptor: acyl donor), enzyme loading (g), quantity of 4Å molecular sieve (g), reaction time (hr) and agitation speed (rpm) significantly affected the esterification and only reaction temperature (°C) did not. Melting point for the methyl 6-O-hexadecanoyl-α-D-glucopyranoside was the highest at 81 °C followed with methyl 6-O-tetradecanoyl α-D-glucopyranoside at 80 °C and the lowest was recorded by methyl 6-O-dodecanoyl-α-D-glucopyranoside at 73 °C.Methyl 6-O-hexadecanoyl-α-D-glucopyranoside, methyl 6-O-tetradecanoyl-α-Dglucopyranoside and methyl 6-O-dodecanoyl-α-D-glucopyranoside had melting enthalpy of 34.8 kJ mol-1, 48.0 kJ mol-1 and at 40.9 kJ mol-1 respectively. For the melting entropy, the values for methyl 6-O-hexadecanoyl-α-D-glucopyranoside was 0.43 kJ mol-1 °C-1, methyl 6-O-tetradecanoyl-α-D-glucopyranoside 0.60 kJ mol-1 °C-1 and methyl 6-O-dodecanoyl α-D-glucopyranoside 0.55 kJ mol-1 °C-1. Liquid crystal properties of the synthesized carbohydrate ester synthesized were evaluated via Optical Polarized Microscopy (OPM). It was found that the liquid crystal textures for monosubstituted carbohydrate ester were of smectic phase. Evaluation on the maximum water mass contained in a quarternary system (carbohydrate ester/n-butanol/nhexadecane/water) was done through a pseudoternary phase diagram. Phase diagram showed maximum 34% water contained in monophasic region of methyl 6-Otetradecanoyl- α-D-glucopyranoside and maximum of 52% water contained in a monophasic methyl-6-O-dodecanoyl-α-D-glucopyranoside. For methyl-6-Ododecanoyl- α-D-glucopyranoside, its concentration at aggregation was 5.2 x 10-4 mM, with minimum air/ water surface tension of 26 mN m-1. Gibbs energy of micellization was calculated at -50 kJ mol-1. Maximum adsorption density of methyl 6-O-dodecanoyl- α-D-glucopyranoside was determined at 4 x 10-6 mol m-2 while its mimimum area per surfactant molecule at air/ water surface was 47 Å2.